Implementation of the novel multiple-input multiple-output power conversion system for applications in a micro-grid - R. Banupriya; R. Nagarajan; K.R.N. Kalis; J. Manjushree Kumari (Automatika)
A novel dual-input dual-output power conversion system is suitable for microgrid applications. The proposed system draws power from solar PV and 1φ AC source and delivers power to 48 V DC load, 24 V intermediate and 12 V busbar, where a battery is connected. The SPVS is connected as input of the first stage of relift Luo converter. The charge/discharge of the battery is managed using a buck-boost converter. The Sliding Mode type of MPPTcontroller is used by the battery control buck-boost converter. The two switches in the buck-boost converter regulate the intermediate LV output voltage at 24 V while charging/discharging the battery. The voltage at the 48 V channel is regulated by the manipulation of the relift Luo converter. The objectives of the system are to ensure MPPT for the SPV source, regulation of 24 V at the intermediate stage and 48 V at the main output and the control of charging/discharging of the battery. The diode bridge rectifier followed by the boost converter acts as PF-corrected rectifier and it delivers 24 V across the intermediate 24 V busbar and the AC source side PF is unity by the hysteresis controller. The results obtained from the simulations done in MATLAB and the experimental prototype validate the proposed idea.